دور استراتيجية المحيط الأزرق في مهام إدارة علاقات الزبائن : دراسة استطلاعية في الشركة الوطنية لصناعة الأثاث المنزلي بالموصل - وجدان حسن حمودي (PROSPECTIVE RESEARCHES, 2023)
Contemporary organizations Face large competition in the market because of the multiplicity and diversity of supply commodity as well as the growing wishes and needs of customers significantly as a result of this development. A matter, which lead the organizations to try to find ways to enable them to face the competition and stay in the market and gain customers. The Blue Ocean Strategy is a strategy used as a way to escape to safe- places with no competition; the current research tries to highlight the role of this strategy through a survey made in one of the industrial companies in the city of Mosul. The survy include a questionnaire which was distributed to administrators. Data analysis produces a set of conclusions which focus on the role of this strategy to support the direction the company to face its competitors. In the light of this, a set of recommendations is presented to strengthen these trends. One of them is that companies which seek survival and excellence must make use of the blue ocean strategy to enhance its competitive position through its approach to managing its relationship with customers.